Genome-wide evolution and expression analysis of the MYB-CC gene family in Brassica spp. - Gu, Bin-Jie; Tong, Yi-Kai; Wang, You-Yi; Zhang, Mei-Li; Ma, Guang-Jing; Wu, Xiao-Qin; Zhang, Jian-Feng; Xu, Fan; Li, Jun; Ren, Feng (PeerJ, 2022)
The MYB-CC family is a subtype within the MYB superfamily. This family contains an MYB domain and a predicted coiled-coil (CC) domain. Several MYB-CC transcription factors are involved in the plant’s adaptability to low phosphate (Pi) stress. We identified 30, 34, and 55 MYB-CC genes in Brassica rapa, Brassica oleracea, and Brassica napus, respectively. The MYB-CC genes were divided into nine groups based on phylogenetic analysis. The analysis of the chromosome distribution and gene structure revealed that most MYB-CC genes retained the same relative position on the chromosomes and had similar gene structures during allotetraploidy. Evolutionary analysis showed that the ancestral whole-genome triplication (WGT) and the recent allopolyploidy are critical for the expansion of the MYB-CC gene family. The expression patterns of MYB-CC genes were found to be diverse in different tissues of the three Brassica species. Furthermore, the gene expression analysis under low Pi stress revealed that MYB-CC genes may be related to low Pi stress responses. These results may increase our understanding of MYB-CC gene family diversification and provide the basis for further analysis of the specific functions of MYB-CC genes in Brassica species.
Keywords: MYB-CC; Evolution; Brassica; Diploid; Allotetraploid